"I am a Responsible Leader" Responsible Corporate Social Responsibility: The Example of Luxembourg. Issue 1 (January 2020) - Schinzel, Ursula
Abstract: This article examines the links between responsible leadership and corporate social responsibility (CSR) in one country, the Grand Duchy of Luxembourg, a linguistically and culturally specific country, and how they are perceived to be enacted or not. The purpose of this study is to combine Hofstede's cross-cultural research with a research on responsible leadership and CSR in Luxembourg, in order to determine if there are any particularities that apply only in the country. In this qualitative study from Spring/Summer 2017, 64 semi-structured interviews were conducted mainly in four culturally different categories. This study is combined with the results of a 2016 study "What is responsible leadership in Luxembourg." Findings indicate that language is used as a key identifier, affecting CSR outcomes, and point to high uncertainty avoidance levels in Luxembourg as a possible reason for lack of change and innovation. Finally, the article discusses the various implications of the findings.